2017
DOI: 10.4174/astr.2017.92.3.123
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical characteristics of papillary thyroid carcinoma arising from the pyramidal lobe

Abstract: Purpose Papillary thyroid carcinoma (PTC) arising from the pyramidal lobe is rare; therefore, clinicopathologic evaluation is lacking. In addition, the rate of occult malignancy in the pyramidal lobe after thyroid surgery is unclear. This study is to evaluate the clinical characteristics of PTCs that involve the pyramidal lobe. Methods The study enrolled 1,107 patients who underwent thyroid surgery for PTC at Seoul National University Hospital from 2006 to 2015. Pyramid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Sporadic cases of primary (instead of recurrent) PTC from the pyramidal lobe were reported. [1316] Yoon et al enrolled 1107 patients with PTC in his study, finding the prevalence of occult malignancy in surgically resected pyramidal lobe tissue was 3.56%. [13] Ha et al reported a 48-year-old woman with primary PTMC in the PL and both thyroid lobes, and total thyroidectomy and central compartment neck dissection were performed for this patient.…”
Section: Discussion and Lessonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sporadic cases of primary (instead of recurrent) PTC from the pyramidal lobe were reported. [1316] Yoon et al enrolled 1107 patients with PTC in his study, finding the prevalence of occult malignancy in surgically resected pyramidal lobe tissue was 3.56%. [13] Ha et al reported a 48-year-old woman with primary PTMC in the PL and both thyroid lobes, and total thyroidectomy and central compartment neck dissection were performed for this patient.…”
Section: Discussion and Lessonsmentioning
confidence: 99%
“…[1316] Yoon et al enrolled 1107 patients with PTC in his study, finding the prevalence of occult malignancy in surgically resected pyramidal lobe tissue was 3.56%. [13] Ha et al reported a 48-year-old woman with primary PTMC in the PL and both thyroid lobes, and total thyroidectomy and central compartment neck dissection were performed for this patient. [16] Santrac et al enrolled 753 patients with PTC from 2003 to 2013 in his institution, but only 3 patients (0.4%) suffered from solitary PTC primarily from the PL.…”
Section: Discussion and Lessonsmentioning
confidence: 99%
“…Hence, it may be afflicted in generalized thyroid disease as well as multifocal thyroid carcinoma [6,7,10]. The PL has been reported as the primary site of papillary and folliculary thyroid carcinoma in multiple case series [11][12][13][14]. Although rare, papillary thyroid carcinoma arising from the PL was significantly associated with a more frequent lymphatic invasion, a higher tumor stage and a more advanced American Joint Committee on Cancer (AJCC) stage when compared to papillary carcinoma found elsewhere in the thyroid gland.…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, papillary thyroid carcinoma arising from the PL was significantly associated with a more frequent lymphatic invasion, a higher tumor stage and a more advanced American Joint Committee on Cancer (AJCC) stage when compared to papillary carcinoma found elsewhere in the thyroid gland. Prevalence of papillary thyroid cancer stemming from or afflicting the PL was 4.4% (49/1107) [13]. Owing to its mostly delicate size, the PL may be overlooked during surgery and may be a potential site for recurrent disease [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Remnant tissue after surgical operation may complicate the proper treatment of such diseases and the sensitive postoperative follow-up of patients. Based on its high incidence, the pyramidal lobe is considered as a normal component of the thyroid gland that may be affected by the diseases that affect the rest of the thyroid parenchyma and uncommonly harbor malignant disease ( 2 ). Anatomic variations of the gland, remnant pyramidal lobes, preclude complete removal of thyroid tissue, which can cause recurrent goiter.…”
mentioning
confidence: 99%